Museum metabarcoding: A novel method revealing gut helminth communities of small mammals across space and time. Issue 13 (November 2018) - Greiman, Stephen E.; Cook, Joseph A.; Tkach, Vasyl V.; Hoberg, Eric P.; Menning, Damian M.; Hope, Andrew G.; Sonsthagen, Sarah A.; Talbot, Sandra L.
Graphical abstract: Highlights: We provide a proof of concept for identification of helminth communities within museum samples. A novel metabarcoding approach amplified helminth DNA from various fixed samples. Multi-locus metabarcoding provides a more holistic view of the shrew gut helminth community. Abstract: Natural history collections spanning multiple decades provide fundamental historical baselines to measure and understand changing biodiversity. New technologies such as next generation DNA sequencing have considerably increased the potential of museum specimens to address significant questions regarding the impact of environmental changes on host and parasite/pathogen dynamics. We developed a new technique to identify intestinal helminth parasites and applied it to shrews (Eulipotyphla: Soricidae) because they are ubiquitous, occupy diverse habitats, and host a diverse and abundant parasite fauna. Notably, we included museum specimens preserved in various ways to explore the efficacy of using metabarcoding analyses that may enable identification of helminth symbiont communities from historical archives. We successfully sequenced the parasite communities (using 12S mtDNA, 16S mtDNA, 28S rDNA) of 23 whole gastrointestinal tracts. All gastrointestinal tracts were obtained from the Museum of Southwestern Biology, USA, and from recent field collections, varying both in time since fixation (ranging from 4 months to 16 years) and preservation method (70% or 95% ethanol stored at room temperature, or flash frozen in liquid nitrogen and stored at −80 °C). Our proof of concept demonstrates the feasibility of applying next generation DNA sequencing techniques to authoritatively identify the parasite/pathogen communities within whole gastrointestinal tracts from museum specimens of varying age and fixation, and the value of future preservation of host-associated whole gastrointestinal tracts in public research archives. This powerful approach facilitates future comparative examinations of the distributions and interactions among multiple associated groups of organisms through time and space.